A 20 dollar note: 'success stories' of Swedish business actors with Iranian origin. (3rd March 2020) - Leivestad, Hege Høyer; Olsson, Erik
ABSTRACT: This article examines the career narratives of entrepreneurs with migrant background in the Swedish business sector. Statistics show that the proportion of individuals with a migrant background who reach so-called top-positions in Swedish society is in general low. Migrants with Iranian background is an exception as many of them have reached high positions as professionals in business corporations and themselves established high-profile businesses in Sweden. Based on in-depth interviews with entrepreneurs and managers with Iranian origin, we will in this article look at how their background is made relevant when reflecting upon professional success and failure. The article is concerned with their exceptional professional achievements and, in particular, the individuals' positioning in relation to their 'society of migration', their society of origin, and the social networks are embedded in as migrants with an Iranian origin. The article shows how narratives of success tend to emphasize the struggles of a 'lonely fighter' while at the same time dismiss discrimination as an explanatory factor. The entrepreneurs' success stories nevertheless focus on how one's career path as innovators and 'agents of social change' is intimately linked with a migrant past and experience.